2022
DOI: 10.1371/journal.pone.0277920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of microaneurysms as predictors of therapeutic response to anti-VEGF therapy in patients with DME

Abstract: Administration of intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy is the first-line therapy for diabetic macular oedema (DME). However, some patients show no or insufficient response to repeated anti-VEGF injections. Therefore, it is necessary to identify factors that can predict this resistance against anti-VEGF treatment. Presence of microaneurysms (MAs) is a predictor of the development and progression of DME, but its relationship with the treatment response to the anti-VEGF agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Indeed, increased CST was more frequently observed around microaneurysms 16 nd a recent analysis published in literature demonstrated that the use of anti-VEGF decreased the numbers of microaneurysms in patients with DME. 7 We demonstrate in the current analysis that the numbers of microaneurysms was halved by the end of the follow-up period, probably explaining the sustained anatomical response to the molecule. The same conclusions can be drawn with hard exudate quanti cation which showed a signi cant decrease in surface area between baseline and the end of follow-up.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Indeed, increased CST was more frequently observed around microaneurysms 16 nd a recent analysis published in literature demonstrated that the use of anti-VEGF decreased the numbers of microaneurysms in patients with DME. 7 We demonstrate in the current analysis that the numbers of microaneurysms was halved by the end of the follow-up period, probably explaining the sustained anatomical response to the molecule. The same conclusions can be drawn with hard exudate quanti cation which showed a signi cant decrease in surface area between baseline and the end of follow-up.…”
Section: Discussionmentioning
confidence: 49%
“…The primary outcome measure was the change in BCVA at 12 months. Secondary outcome measures were the proportion of patients who gained ≥ 15 letters from baseline to month 12, CST changes at 12 months, the change in microaneurysms numbers from baseline to 12 months counted on early, and late phases of uorescein angiography as previously described, 7 and the change in hard exudates area on fundus retinography using ImageJ (available in the public domain at https://imagej.nih.gov/ij/download.html Institute of Health, USA) according to the algorithm previously described. 8 Ocular hypertension (OHT) was de ned as IOP > 25 mmHg and/or an increase of 10 mmHg from baseline over the follow-up period.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Makoto Hatano et al demonstrated that detection of MAs in the nasal macula using pretreatment indocyanine green angiography may indicate resistance to anti-VEGF therapy in DME patients. The presence of large MAs in the nasal macula indicates that the DME condition is physiologically and anatomically severe, and such cases are likely to resist anti-VEGF therapy [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the evaluation of MAs pre-and post-anti-EGF therapy may have clinical implications for decision making. Hanato M et al, using indocyanine green angiography (IA), found that non-responders to anti-VEGF therapy had a higher number of pre-treatment nasal macular MAs [44]. Additionally, Mori et al found that the number of MAs in late-phase IA at baseline and at six months was significantly higher in patients who had a recurrence of DME after treatment [45].…”
Section: Vd Changes During Dme Treatmentmentioning
confidence: 99%